Vietnam War: A Study of History, Causes, and Impact - Narahara, Sean; Prakoso, Lukman Yudho; Alam, Tasdik Mustika (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The Vietnam War was one of the most controversial and influential military conflicts of the 20th century. This journal article aims to provide an in-depth analysis of the history, causes, and impact of the war that raged in Vietnam from 1955 to 1975. Using primary and secondary sources, the author investigates various aspects of the conflict, including the historical context, the underlying reasons for the outbreak of the war, and far-reaching consequences that continue to shape regional and global affairs to this day. Cold War rivalry between the United States and the Soviet Union also played an important role, with the US supporting the South Vietnamese government to prevent the spread of communism in Southeast Asia. Apart from that, the methodology used in this research is a descriptive qualitative method. This method is applied by reviewing various literature related to this research topic. Thus, the role of nationalism and regional dynamics contribute to the escalation of hostilities in the region. These events had significant implications for the trajectory of the conflict and shaped public opinion both in the countries involved and internationally.